Hydrogen Homes Dataset 2022 - Gordon, Joel; Balta-Ozkan, Nazmiye; Nabavi, Seyed Ali (Cranfield University, 2023)
These files present data gathered on public perceptions of hydrogen homes (i.e. appliances for heating and cooking purposes) in the United Kingdom, following a broadly nationally representative survey (N = 1845) conducted between 06/10/2023 and 23/12/2023. All survey responses were measured using either a five-point or eleven-point Likert scale. The survey questions are provided alongside the recorded responses.
Keywords: 'Domestic hydrogen'; 'Social acceptance'; 'Public trust'; 'Environmental attitudes'; 'Hydrogen heating and cooking'; 'Perceived risks; costs and benefits'